Cavernous Sinus Dural Fistulae Treated by Transvenous Approach through the Facial Vein: Report of Seven Cases and Review of the Literature - Biondi, Alessandra; Milea, Dan; Cognard, Christophe; Ricciardi, Giuseppe K.; Bonneville, Fabrice; van Effenterre, Rémy (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Dural Carotid Cavernous Fistulas (CCFs) can be treated by transarterial and/or transvenous endovascular techniques. The venous route usually goes through the internal jugular vein (IJV) and the inferior petrosal sinus (IPS) up to the pathologic shunts of the cavernous sinus. In case a thrombosed IPS, catheterization through the obstructed sinus is not always possible and a puncture of the superior ophthalmic vein (SOV) can be performed often after a surgical approach. We report our results in the endovascular transvenous treatment of dural CCFs through the facial vein (retrograde catheterization of the IJV, facial vein, angular vein, SOV, and cavernous sinus).METHODS: A retrospective study of seven patients with a dural CCF treated with transvenous embolization via the facial vein was performed. In five patients, the IPS was thrombosed. In one patient, the IPS was patent, but there was not communication between the cavernous sinus compartment in which the CCF shunts were located and the IPS itself. In the only patient with the CCF draining through permeable IPS, the transvenous route through the IPS permitted the occlusion of the posterior CCF shunts and a second session was performed through the facial vein in order to occlude the shunts of the anterior compartment of the cavernous sinus. The other six patients underwent one embolization session only.RESULTS: In all seven cases, it was possible to navigate through the tortuous junction of the angular vein and the SOV. In one patient with a thrombosed SOV, the venous procedure was interrupted because the catheterization through the occluded SOV failed. In the other six patients, after transvenous catheterization of the cavernous sinus via the facial vein, placement of coils resulted in complete occlusion of the dural CCF with clinical cure in four patients and improvement in two.CONCLUSION: In the endovasular treatment of the dural CCFs, the transfemoral approach via the facial vein provides a valuable alternative to other transvenous routes. Catheterization of the cavernous sinus via the facial vein is usually successful. Although this technique requires caution, it allows a safe and effective treatment of these lesions.